WAYS TO EFFECTIVELY USE SMARTPHONES IN WORKING WITH GIFTED STUDENTS IN BIOLOGY LESSONS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Working with gifted students involves the identification and development of the natural inclinations and creative potential of each child, the realization of his inclinations and capabilities. The article is devoted to the problems of digitalization of secondary education, the study of the possibilities of modern digital technologies, the description of the feasibility of their application in secondary school and promising areas of development and use. The article describes ways to effectively use device in working with gifted students in biology lessons. At the same time, the necessity of a systematic approach to solving this problem is explained.